1967
DOI: 10.1007/bf02045594
|View full text |Cite
|
Sign up to set email alerts
|

Lethal germination of spores ofBacillus megaterium 9885

Abstract: S L~K R Y . The ultrastructure of free spore coats of Bacillus megaterium 9885 was studied by exploitation of the spontaneous lysis of newly germinated spores in the presence of phosphate and absence of Ca*+, and the subsequent release of coat subunits. The subunits appeared as the middle layer of a sandwich. The primary size of the subunits was c. 20nm. Negative staining suggested the presence of peripheral charged groups (carboxyl?) surrounding a hexagonal-shaped subunit containing an acentric electron opaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The question naturally arises as to why the spores of B. megaterium ATCC 9885 undergo complete lysis when exposed to lysozyme. Others (4,12) have already demonstrated that complete lysis of the spores of this strain may occur with so-called physiological germinants. In complex mixtures of germinants, the presence of phosphate and of L-leucine was reported to be conducive to lysis, whereas calcium ions exerted a protective effect (12).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The question naturally arises as to why the spores of B. megaterium ATCC 9885 undergo complete lysis when exposed to lysozyme. Others (4,12) have already demonstrated that complete lysis of the spores of this strain may occur with so-called physiological germinants. In complex mixtures of germinants, the presence of phosphate and of L-leucine was reported to be conducive to lysis, whereas calcium ions exerted a protective effect (12).…”
Section: Resultsmentioning
confidence: 94%
“…Others (4,12) have already demonstrated that complete lysis of the spores of this strain may occur with so-called physiological germinants. In complex mixtures of germinants, the presence of phosphate and of L-leucine was reported to be conducive to lysis, whereas calcium ions exerted a protective effect (12). Therefore, we have carried out preliminary experiments directed to this question of lysozyme-sensitivity of the spore central body.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It seems likely that a substance which scavenges ions from outside the cell, but which cannot be found cell free in any quantity except from stationary phase or disrupted cultures, may perform both extra-and intracellular functions which depend on efficient transport of the substance to and from the cell, thus distinguishing the biological from chemical chelating agents. Calcium is an important structural cation of cell walls (Humphrey & Vincent, 1966) and plays a vital role in preserving the integrity of the new vegetative cells of gmminated spores (Holdom & Foster, 1967). Calcium also is known to complex strongly with large protein molecules (Reithal, 1963).…”
Section: Discussionmentioning
confidence: 99%